Decentralization with porous borders: Public production in a federation with tax competition and spillovers - Stephanie Armbruster; Beat Hintermann (University of Basel, Center of Business and Economics (WWZ), 2019)
We analyze the strategic interaction of regional and federal governments using a model that includes fiscal externalities in the form of inter-regional capital tax competition and technical externalities in the form of inter-regional spillovers. The federal government aims to correct for these inefficiencies using a transfer system. If the regional governments are policy leaders (such that federal policy is set conditional on regional choices), they will internalize both fiscal and technical externalities but free-ride on the transfer system. Efficiency can be achieved by introducing a second transfer scheme that is independent of regional public production. If the federal government sets its policy first and can commit itself to it, the outcome is efficient only if matching grants are used that are financed outside of the transfer system.
Keywords: H21; H40; H77; Q58; 330; Fiscal federalism; tax competition; externalities; spillovers; commitment; centralized leadership; decentralized leadership